1990
DOI: 10.1111/j.1365-2125.1990.tb03839.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep laboratory studies on single dose effects of suriclone.

Abstract: 1 In a double-blind, placebo-controlled sleep laboratory study single doses of suriclone, a new non-benzodiazepine anxiolytic binding to benzodiazepine receptors, were investigated with respect to sleep and awakening. 2 Sixteen healthy young volunteers spent 10 nights in the sleep laboratory: 1 adaptation night, 1 baseline night and 4 drug nights (placebo; 0.2 mg, 0.4 mg suriclone; 2 mg lorazepam as reference drug) and 4 subsequent wash-out nights (drug-interval: 1 week). Somnopolygraphic investigations (22.30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…After 0.2 mg suriclone we observed even an improvement in complex reaction, a shortening of reaction time, a decrease of errors in the reaction time task, an increase of correct calculations in the Pauli test, as well as an improvement in the psychomotor activity. Indeed, an improvement in noopsychic functions as measured in attention was described in our sleep laboratory studies when we measured objective awakening qualities in the morning after bedtime medication of suriclone [9].…”
Section: Mg)mentioning
confidence: 66%
See 2 more Smart Citations
“…After 0.2 mg suriclone we observed even an improvement in complex reaction, a shortening of reaction time, a decrease of errors in the reaction time task, an increase of correct calculations in the Pauli test, as well as an improvement in the psychomotor activity. Indeed, an improvement in noopsychic functions as measured in attention was described in our sleep laboratory studies when we measured objective awakening qualities in the morning after bedtime medication of suriclone [9].…”
Section: Mg)mentioning
confidence: 66%
“…As also the attenuation of the total power, the decrease of alpha activity and the slowing of the centroid of the beta frequency band was more pronounced after the reference compound than suriclone, it may be hypothesized that the investigated doses of 0.1-0.4 mg suriclone are less sedative than 1 mg alprazolam. Indeed, in a recent sleep study concerning the acute effects of single doses of 0.2 mg and 0.4 mg suriclone, compared with 2 mg lorazepam, we noted that 0.2 mg suriclone did not induce any alterations in the all-night sleep, while after 0.4 mg suriclone and 2 mg lorazepam nocturnal awakenings decreased significantly, compared with placebo, which was reflected in an improved subjective sleep quality [9]. In the morning, well-being, drowsiness and reaction time performance deteriorated after 2 mg lorazepam, compared with placebo, but not after suriclone.…”
Section: Mg)mentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, 0.1 mg and 0.2mg suriclone exhibited no sedative properties in various thymopsychic variables, while 0.4 mg suriclone and 1 mg alprazolam produced a deterioration, which was also reflected to some extent in EEG analyses. In a sleep study (Saletu et al 1990), single doses of 0.2 mg and 0.4 mg suriclone were superior to 2 mg lorazepam with respect to well-being, reaction time performance in the morning, subjective awakening quality, emotional rapport, drowsiness and attention (Saletu et al 1990) The complex and still unresolved relationship of the structure and function of the GABA receptor to psychiatry has been discussed recently by Zorumski and Isenberg (1991). In this review, the authors mention the possibility that sedative and anxiolytic effects are mediated by different receptor subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Since the RIA method used for the suriclone assay also responds to suriclone metabolites, we subsequently "bioassayed" (Mattila, unpublished data) the plasma samples for suriclone and zopiclone, in diazepam equivalents, with a direct radioreceptor assay [25]. It appeared that suriclone concentrations were low or even undetectable, and the levels were similar at 2 and 4 h. Saletu et al [26] found that suriclone 0.4 mg improved sleep quality whereas 0.2 mg did not. No residual effects were detected in the morning following the intake of 0.4 mg suriclone at night.…”
Section: Discussionmentioning
confidence: 99%